2022
DOI: 10.1111/jfpp.16561
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of microfluidized sugarcane juice and associated kinetics

Abstract: Microfluidization was used as a mechanical method for the preservation of sugarcane juice. Sugarcane juice was microfluidized at 159 MPa/1 cycle and packed in glass bottles and high-density polyethylene (HDPE) stand-up pouches along with a control. The control and microfluidized samples that were stored at 25°C, and control stored at 4°C showed spoilage on the second day and were discarded. A reduction in total soluble solids, pH, and sensory score along with an increase in reducing sugars, polyphenol oxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The change in the RS of AALTHC processed sugarcane juice is observed to be statistically non‐significant ( p > 0.01) up to the 21st day; however, a steep decrease can be seen thereafter that continued till the end of storage (56 days) under refrigerated conditions. This is in line with the study by Tarafdar and Kaur (2022), where reducing sugars of microfluidized sugarcane juice declined during storage. The results showed that the RS fitted better with the second‐order reaction models ( R 2 = .933), followed by the first‐order reaction models and the zero‐order models at refrigeration conditions (Table 2).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The change in the RS of AALTHC processed sugarcane juice is observed to be statistically non‐significant ( p > 0.01) up to the 21st day; however, a steep decrease can be seen thereafter that continued till the end of storage (56 days) under refrigerated conditions. This is in line with the study by Tarafdar and Kaur (2022), where reducing sugars of microfluidized sugarcane juice declined during storage. The results showed that the RS fitted better with the second‐order reaction models ( R 2 = .933), followed by the first‐order reaction models and the zero‐order models at refrigeration conditions (Table 2).…”
Section: Resultssupporting
confidence: 93%
“…The increase in RS during the storage period may be due to acid hydrolysis of sugars to the degradation of disaccharides to monosaccharides, resulting in increased RS along with the formation of deteriorative by‐products such as furfural, cellobiose, and hydroxymethylfurfural (Sankhla et al, 2012; Sirohi et al, 2020; Sreedevi et al, 2020). Invertase activity could also be responsible for the conversion of sucrose to glucose and fructose, resulting in increased RS and undesirable sweetness (Huang et al, 2015; Mao et al, 2007; Tarafdar & Kaur, 2022). The change in the RS of AALTHC processed sugarcane juice is observed to be statistically non‐significant ( p > 0.01) up to the 21st day; however, a steep decrease can be seen thereafter that continued till the end of storage (56 days) under refrigerated conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pH, TSS, and acidity best fit into the second‐order equation, whereas total sugars, sucrose, and CO 2 best fit into the first‐order equation under refrigerated storage conditions. The storage stability of microfluidic sugar cane juice in a glass bottle and high‐density polyethylene pouch was studied by Tarafdar and Kaur (2022), and results showed changes in pH, TSS, and dextran best fit in the zero‐order model. Pandiselvam et al (2021) studied the reaction kinetics of coconut sap on storage for 6 h. They reported that the R 2 value is ≥0.90 for all the three models for change in pH, TSS, acidity, and turbidity.…”
Section: Resultsmentioning
confidence: 99%